Meta-analysis identified the TNFA -308G > A promoter polymorphism as a risk factor for disease severity in patients with rheumatoid arthritis - Toonen, Erik JM (BioMed Central, 2012)
INTRODUCTION: The goal of this study is to investigate whether the -308G > A promoter polymorphism in the tumor necrosis factor alpha (TNFA) gene is associated with disease severity and radiologic joint damage in a large cohort of patients with rheumatoid arthritis (RA). METHODS: A long-term observational early RA inception cohort (n = 208) with detailed information about disease activity and radiologic damage after 3, 6 and 9 years of disease was genotyped for the TNFA -308G > A promoter polymorphism (rs1800629). A longitudinal regression analysis was performed to assess the effect of genotype on RA disease severity and joint damage. Subsequently, a meta-analysis, including all publically available data, was performed to further test the association between joint erosions and the TNFA polymorphism. To learn more about the mechanism behind the effect of the polymorphism, RNA isolated from peripheral blood from RA patients (n = 66) was used for TNFA gene expression analysis by quantitative PCR. RESULTS: Longitudinal regression analysis with correction for gender and disease activity showed a significant difference in total joint damage between GG and GA+AA genotype groups (P = 0.002), which was stable over time. The meta-analysis, which included 2,053 patients, confirmed an association of the genetic variant with the development of erosions (odds ratio 0.78, 95% CI 0.62, 0.98). No significant differences in TNFA gene expression were observed for the different genotypes, confirming earlier findings in healthy individuals. CONCLUSIONS: Our data confirm that the TNFA -308G > A promoter polymorphism is associated with joint damage in patients with RA. This is not mediated by differences in TNFA gene expression between genotypes.